Teen Titans: Beast Boy - Book 2 - Garcia, Kami; Picolo, Gabriel; Haynes, Rob; Downie, Gabriela (Burbank, CA : DC Ink, 2020)
Seventeen-year-old Garfield Logan finally impresses the social elite at his high school, but popularity comes at a price when he undergoes sudden physical changes as the dares from his new friends escalate.
"Beast Boy created by Arnold Drake."
Ages 13-17.
Keywords: Beast Boy -- (Fictitious character) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Popularity -- Comic books, strips, etc; Social acceptance -- Comic books, strips, etc; High schools -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Animal experimentation -- Comic books, strips, etc; Human experimentation in medicine -- Comic books, strips, etc; Shapeshifting -- Comic books, strips, etc; Popularity -- Fiction; High schools -- Fiction; Schools -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Young adult works; Fiction; Superhero comics; Coming-of-age comics; Comics (Graphic works); Bildungsromans; Graphic novels; Graphic novels; Graphic novels; Bildungsromans; Comics (Graphic works); Superhero comics; Coming-of-age comics